2019
DOI: 10.1021/acs.cgd.9b00593
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Optoelectronic Properties of the α-, β-, and γ-Glycine Polymorphs and the Glycine Dihydrate Crystal: A DFT Study

Abstract: Density functional calculations were performed to study the properties of the three main glycine solid-state polymorphs α, β, and γ and the glycine dihydrate (GDH) crystal. Optimized unit cell geometries, Kohn–Sham electron energy bands, electron densities of states, population charges, carrier effective masses, optical absorption, and complex dielectric functions were obtained for each glycine system using a GGA functional plus the TS dispersion correction, leading to lattice parameters very close to the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 78 publications
0
20
0
Order By: Relevance
“…In general, PBE + D3 calculations provided a good description of the structural parameters, probably due the gradient corrected exchange-correlation functional. Rodríguez et al reported PBE + TS results, in which the unit cell volume error was only 0.37% for the α phase and a maximum deviation of 1.4% in the lattice parameters was obtained for the α and β-glycine, whereas noncorrected PBE functional overestimated the lattice parameters, leading to higher deviations in comparison to the experimental data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, PBE + D3 calculations provided a good description of the structural parameters, probably due the gradient corrected exchange-correlation functional. Rodríguez et al reported PBE + TS results, in which the unit cell volume error was only 0.37% for the α phase and a maximum deviation of 1.4% in the lattice parameters was obtained for the α and β-glycine, whereas noncorrected PBE functional overestimated the lattice parameters, leading to higher deviations in comparison to the experimental data.…”
Section: Resultsmentioning
confidence: 99%
“…Accurate result for the stability ranking has been reported from PBE calculations including the Grimme’s dispersion correction scheme (D2), using a genetic algorithm code . However, such results could not be reproduced by the CPAZ , + TS calculations in the work of Rodríguez et al…”
Section: Introductionmentioning
confidence: 99%
“…[34] glycine at ambient and high pressures was attempted many times. [48][49][50][51][52] Some recent papers propose the structures of some new polymorphs, but their existence has never been confirmed experimentally. [53,54] In all the glycine polymorphs there is a common structureforming motif -a head-to-tail hydrogen-bonded chain formed by the glycine zwitter-ions (Figure 4a).…”
Section: Figurementioning
confidence: 99%
“…[52,[127][128][129][130][131][132] The number of theoretical works dedicated to the interactions of glycine with its environment in the gas phase, various fluids and in various crystal structures is as large as that of various experimental studies on this compound. [48,50,52,73,91,93,[133][134][135] However, it is hardly possible to select an obviously dominating type of the interaction. In a text-book by Kitaigorodsky [136] a layer in the glycine structure is shown as an example of a "close packing principle", so that van der Waals interactions are optimized.…”
Section: Intermolecular Interactionsmentioning
confidence: 99%
“…At temperatures higher than 440 K, αglycine becomes more stable than γ-glycine. The crystal structure and relative stabilities of the glycine polymorphs have been studied extensively, using different computational methods [81][82][83][84][85][86][87].…”
Section: Glycinementioning
confidence: 99%